Internalizing/Externalizing Problems: Review and Recommendations for Clinical and Research Applications - Achenbach, Thomas M; Ivanova, Masha Y; Rescorla, Leslie A; Turner, Lori V; Althoff, Robert R (Journal of the American Academy of Child and Adolescent Psychiatry, 2016)
More than 75,000 articles have been published on internalizing and externalizing problems. To advance clinical and research applications of internalizing/externalizing concepts and data, our objectives were as follows: to provide an overview of recent research on internalizing/externalizing problems assessed at ages 1½ to 18 years; to identify issues raised by methods for assessing such problems; and to develop recommendations for more precise, consistent, informative, and productive assessment of such problems. A total of 4,870 peer-reviewed articles published from January 1, 2012 through December 31, 2014 were systematically reviewed and identified by the search terms "internalizing" or "externalizing," followed by detailed coding of 693 articles that reported use of measures meeting criteria for methodologically sound assessment of internalizing/externalizing problems. Many articles reported data based on measures that did not meet criteria for methodologically sound assessment of internalizing/externalizing problems. The 693 articles that used measures meeting criteria for methodological soundness and that qualified for detailed coding reported findings for 649,457 children living in 65 societies on all inhabited continents. Data were obtained from parents, teachers, children, clinicians, caregivers, and others. Samples included general population, clinical, school, at-risk, multicultural, welfare, and various ethnic/racial and socioeconomic groups. Many analytic methods were used to test associations of diverse variables with internalizing/externalizing problems. The diverse procedures used to assess internalizing/externalizing problems pose challenges for clinical and research applications. To meet the challenges, recommendations are provided for using assessment instruments supported by published standardization, reliability, validity, and normative data to advance clinical services and research.